Unintended consequences of the innovation policy programmes: social evaluation of the Technological Projects programme in Croatia - Švarc, Jadranka (Array, 2011)
The paper presents empirical results of social evaluation of the first innovation policy programme, Technology Projects (TEST), in Croatia to identify and explain the main bottlenecks of the programme and put them in perspective in terms of the entire innovation system. The motivation is the growing criticism of innovation system's efficiency and perception of poor return on public investment in innovation policy programmes. The proposed method of social evaluation is based on combination of the institutional theory and the sociological approach of intended and unintended consequences. It reveals that expected outcomes of the programme such as commercialisation of research and technological outputs are exchanged, in the majority of projects, for essentially scientific results such as scientific publications and extension of the on-going scientific projects. The reasons are found in the institutional deficits that point to the persistence of some common 'systemic' problems in the innovation system. Their drivers are identified in three types of institutional deficits: administrative rules and procedures, some aspects of social capital and broader socio-economic environment that commonly determine behaviour and interaction of the main stakeholders of the programme.